Prevalence of colistin resistance in clinical isolates of Enterobacteriaceae: A four-year cross-sectional study. Issue 6 (December 2017) - Prim, Núria; Turbau, Miquel; Rivera, Alba; Rodríguez-Navarro, Judith; Coll, Pere; Mirelis, Beatriz
Highlights: Prevalence of colistin resistance in clinical isolates of Enterobacteriaceae was 0.7%. Plasmid-mediated colistin resistance gene mcr-1 was detected only in Escherichia coli. Colistin resistance was not restricted to MDR isolates and to clinical settings. Most colistin-resistant isolates were obtained from patients that had not received colistin previously. Summary: Objectives: The objectives were to determine the prevalence of colistin resistance in clinical isolates of Enterobacteriaceae, and to gain knowledge on the epidemiological and clinical features of the patients. Methods: All colistin-resistant Enterobacteriaceae consecutively isolated from clinical samples in our institution from 2012 to 2015, were included in this cross-sectional study. Intrinsic-resistant species were excluded. Minimum inhibitory concentration was performed by gradient diffusion. Detection of plasmid-encoded colistin resistance genes mcr-1 and mcr-2 was performed by amplification. Epidemiological and clinical features were reviewed. Results: Of 13579 Enterobacteriaceae isolates, 91 were colistin-resistant. The overall prevalence of colistin resistance was 0.67%. The rates were higher in Enterobacter cloacae (4.2%) than Escherichia coli (0.5%) and Klebsiella pneumoniae (0.4%). One third of the isolates were multi-drug resistant (MDR). While mcr-2 was not detected, mcr-1 was detected only in E. coli. Regarding these infections, 23% were community-acquired. 89% of the patients had not received colistin previously. There were no significant differences between infections caused by mcr-1 and non- mcr-1 -carrying isolates. Conclusions: Colistin resistance was not restricted to MDR isolates and to clinical settings. Most patients had no record of previous administration of colistin.